Effect of problem-based learning model on biodiversity problem-solving skills - Ratna Komala; Erna Heryanti; Amelia Rinawati (Biosfer: Jurnal Pendidikan Biologi, 2021)
Problem-solving skill is a way or strategy to achieve goals following good and correct procedures. One of the learning models that can be applied to improve problem-solving skills is a learning model of Problem-Based Learning. The purpose of this research was to determine the effect of the problem-based learning model on student’s problem-solving skills of biodiversity. This research was conducted at SMAN 89 Jakarta in August-September 2019. The method used was a quasi-experiment. The research sample was 66 students of class X MIA with a simple random sampling technique, the instrument used was pretest and posttest in the form of a description question. Instrument of problem-solving skills was tested for validity and reliability. The result of the validity test showed that there were 15 valid items out of 18 items. The reliability test showed that the r-value was 0,901 and included in very high criteria. The effectiveness test of the PBL model with normalized gain calculated score of 0,72 or included in the category of fairly effective. The research result showed that the problem-based learning model influenced students’ problem-solving skills of biodiversity.